THE PURPOSE OBJECTIVES TOOLS STYLES AND BASIC PRINCIPLES OF SPORTS TRAINING - Ibadullaev Balxoja (PEDAGOGS, 2024)
Annotation: At the present stage of the development of society, it is observed that in the multifaceted process of educating a person, developing his physical qualities, strengthening his health, increasing his ability to work, creating a comfortable mental environment in teams, physical education and sports are gaining in importance. Various types of Sports Wrestling, which help to educate physically strong, Restless people, occupy an important place in the system of physical education.